A Prospective Study on Cognitive Impairment in Middle-aged Adults With Newly Diagnosed Celiac Disease. Issue 4 (April 2019) - Longarini, Gabriela; Richly, Pablo; Temprano, M. de la Paz; Costa, Ana F.; Vázquez, Horacio; Moreno, María L.; Niveloni, Sonia; López, Pablo; Smecuol, Edgardo; Mazure, Roberto; González, Andrea; Mauriño, Eduardo; et al.
Abstract : Aims: Our objectives were to: (1) determine whether celiac disease (CD) patients have cognitive impairment at diagnosis; and (2) compare their cognitive performance with nonceliac subjects who have similar chronic symptoms and healthy controls. Materials and Methods: Fifty adults (age range: 18 to 50 y) with symptoms and signs compatible with CD were enrolled in a prospective cohort irrespective of the final diagnosis. At baseline, all individuals underwent cognitive functional and psychological evaluation. CD patients were compared with subjects in whom CD was ruled out and with healthy controls matched by sex, age, and years of schooling. Results: Thirty-three subjects (66%) were diagnosed with CD. Compared with the healthy controls (n=26), CD cases and disease controls (n=17; mostly irritable bowel syndrome) had impaired cognitive performance ( P =0.02 and P =0.04, respectively), functional impairment ( P <0.01), and higher depression ( P <0.01). CD patients had similar cognitive performance and anxiety, but nonsignificant lower depression scores compared with disease controls. Conclusions: Abnormal cognitive functions detected in newly diagnosed CD adult patients seem not to be disease specific. Our results suggest that cognitive dysfunction could be related to the presence of prolonged symptoms due to a chronic disease.